SYNTHESIS NEW POTENTIAL ANTI-INFLAMMATORY AGENT SODIUM SALT OF PENTAGAMAVUNON-0 - Enade Perdana Istyastono; Rr. Sri Untari Siwi S.M.P; Andreas Asdi Utama; Supardjan A.M (Indonesian Journal of Chemistry, 2004)
Inflammation is the response of living tissues to injury. The process affects physiological changes such as erythema, edema, asthma and fever. Non-steroid Anti-inflammatory Drugs (NSAIDs) have been developed since they could inhibit inflammation process because of its ability to inhibit biosynthesis of prostaglandin, one of inflammation mediators, through inhibition of cyclooxigenase (COX) enzymes. Molecules, which have been reported having anti-inflammatory activity, for example, are curcumin, some curcumin derivatives and curcumin analogues. One of curcumin analogues that has been  developed is pentagamavunon-0 (PGV-0) whose IUPAC name is 2,5-bis(4'-hidroxy-3'-methoxy-benzylidene)cyclo-pentanone. But PGV-0, which is like curcumin, practically insoluble in water, so it causes problems in the development. The aim of this research is to synthesize a derivative of PGV-0, a natrium salt of PGV-0 (natrium pentagamavunonate-0/Na-pentagamavunonate-0), which is hoped to have a better anti-inflammatory activity and solubility in water than PGV-0. PGV-0 was synthesized by reacting vanillin and cyclopentanone catalized by acid. Na-pentagamavunonate-0 was synthesized with PGV-0 as a starting material using an appropriate method. This research was able to synthesize new compound that was estimated as a natrium salt of PGV-0 (natrium pentagamavunonate-0/Na-pentagamavunonate-0).